2002
DOI: 10.1017/s1047951100012919
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous aortic valvoplasty in congenital aortic valvar stenosis

Abstract: We have reviewed the largest series of patients in Latin-America reported thus far after undergoing percutaneous aortic valvoplasty, concentrating on mid term follow-up and limitations. New prospective and multicentric studies are needed from our region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…The effectiveness of balloon valvuloplasty with regard to pressure reduction of the left ventricle has been reported by several authors in the past [1][2][3][4]6,7,[10][11][12][13][14]; however, most of those studies are single center experiences or include relatively small numbers of patients [2][3][4]6,7,12,14]. Keeping in mind that indications for and technical performance of balloon valvuloplasty are not standardized and can differ considerably between institutions and even within centers [15], it is remarkable that in the present study the results are to a great extent comparable to those reported from single center studies [2,4,7].…”
Section: Discussionmentioning
confidence: 94%
“…The effectiveness of balloon valvuloplasty with regard to pressure reduction of the left ventricle has been reported by several authors in the past [1][2][3][4]6,7,[10][11][12][13][14]; however, most of those studies are single center experiences or include relatively small numbers of patients [2][3][4]6,7,12,14]. Keeping in mind that indications for and technical performance of balloon valvuloplasty are not standardized and can differ considerably between institutions and even within centers [15], it is remarkable that in the present study the results are to a great extent comparable to those reported from single center studies [2,4,7].…”
Section: Discussionmentioning
confidence: 94%
“…(J Am Coll Cardiol 2010;56:1740-9) © 2010 by the American College of Cardiology Foundation First reported 26 years ago (1), balloon aortic valvuloplasty has become the preferred treatment for newborns, children, and young adults with congenital aortic stenosis (AS) at most centers (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Factors associated with technical success and short-term and midterm outcomes of balloon valvuloplasty for congenital AS have been characterized in a number of studies (2)(3)(4)6,10,11,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…However, this procedure is not free from possible complications. Significant aortic insufficiency, as a result of BAV, is present in 5% to 13% of patients even if the balloon diameter is smaller than the valvular aortic ring [5][6][7]. In our experience, previously published [5], in a sample of 141 patients subject to BAV 10 cases (7%) developed aortic insufficiency grade III or IV after the procedure.…”
Section: Introductionmentioning
confidence: 58%
“…Significant aortic insufficiency, as a result of BAV, is present in 5% to 13% of patients even if the balloon diameter is smaller than the valvular aortic ring [5][6][7]. In our experience, previously published [5], in a sample of 141 patients subject to BAV 10 cases (7%) developed aortic insufficiency grade III or IV after the procedure. The energetic cardiac contractions and the pulsatile flow in the aorta are factors which cause rapid balloon movements when the balloon is inflated at the left outflow tract and favors the presence of aortic insufficiency [8].…”
Section: Introductionmentioning
confidence: 58%